2019
DOI: 10.1186/s12891-019-2599-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the surgical neck fracture of the humerus with a novel external fixator in the elderly with osteoporosis: biomechanical analysis

Abstract: Background No consensus exists on the treatment of proximal humerus fractures, especially in the elderly patients with osteoporosis. This study was aimed to evaluate the biomechanical characteristics of a novel external fixator in treating two-part surgical neck fracture of the proximal humerus in the elderly patients with osteoporosis. Methods Sixteen female elderly humeral shaft specimens with osteoporosis were randomized into 2 groups. Models with the surgical neck t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The cement could provide strength which was between cancellous bone and cortical bone in compressive strength, bending modulus, and bending strength. [ 33 ] In biomechanical study of external fixator, Huang [ 31 ] found that the external fixator seemed to be superior to plate fixation in load bearing and resistance to torsional stress, the ultimate bearing capacity and load bearing were higher in the external fixator group (145.16 ± 17.42 N and 140 N, respectively) than plate group (120.21 ± 13.15 N and 69.63 ± 25.16–90.78 ± 17.18 N, respectively), and in the resistance to torsional stress, the external fixator’s torque fluctuated (within 1 Nm) more evenly distributed than plate’s torque (1–5 Nm), and external fixation provided the better rigidity. Li et al [ 30 ] also found that linking together the ends of fixation wires with external fixator could provide enough stability and could enhance the rotational stiffness of the construct.…”
Section: Discussionmentioning
confidence: 99%
“…The cement could provide strength which was between cancellous bone and cortical bone in compressive strength, bending modulus, and bending strength. [ 33 ] In biomechanical study of external fixator, Huang [ 31 ] found that the external fixator seemed to be superior to plate fixation in load bearing and resistance to torsional stress, the ultimate bearing capacity and load bearing were higher in the external fixator group (145.16 ± 17.42 N and 140 N, respectively) than plate group (120.21 ± 13.15 N and 69.63 ± 25.16–90.78 ± 17.18 N, respectively), and in the resistance to torsional stress, the external fixator’s torque fluctuated (within 1 Nm) more evenly distributed than plate’s torque (1–5 Nm), and external fixation provided the better rigidity. Li et al [ 30 ] also found that linking together the ends of fixation wires with external fixator could provide enough stability and could enhance the rotational stiffness of the construct.…”
Section: Discussionmentioning
confidence: 99%
“…When surgical management of proximal humerus fractures is warranted, there are several surgical approaches available to achieving reduction and fixation of the fracture. Such methods include open reduction and internal fixation with screws and locking plates, intramedullary nailing, hemiarthroplasty, and even reverse total shoulder arthroplasty [2]. Each patient's medical comorbidities should be evaluated before considering if a patient is a candidate for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another comorbidity heavily correlated with proximal humerus fractures is osteoporosis [2]. Poor bone quality is a known predictor of intraoperative and postoperative complications; therefore, if a patient with known osteoporosis requires surgical intervention, careful considerations must be taken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies investigating the morphometry of surgical neck, which is the most frequently fractured part, are almost nonexistent (10,15). While, neck fractures have been a subject to vast numbers of researches (16,17), its structural dispositions depending on the variants of sex and directional morphometry require further investigation. As the preceding studies usually endeavor to investigate humerus length comparisons between the male and female samples, they rarely pay attention to the surgical neck-based comparisons in measurements (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%